Self-replicating Reverse Micelles - Pascale Angelica Bachmann; Pier Luigi Luisi; Jacques Lang (CHIMIA, 1991)
Conditions are described, under which the hydrolysis of octyl octanoate (O-OA) takes place at the interface of reverse micelles fanned by sodium octanoate (OA) in isooctane. Since the micelle-mediated hydrolysis affords fresh OA, which spontaneously assemble into new micelles, the reaction can be seen as a self-replicating process. The kinetics and the spectroscopy of this self-replication process are presented.